METODE PENGUKURAN LUAS DAUN TANAMAN MENGGUNAKAN BANTUAN OBJEK TUNTUN BERBASIS PENGOLAHAN CITRA DIGITAL - Ramadhani, Farchan Mushaf Al; Sajuri, Sajuri; Amin, Rohmatul; Lutfiana, Anisa (Agros Journal of Agriculture Science, 2024)
Leaf area data is required to measure leaf area index and net assimilation. Several existing leaf area measurement methods have advantages and disadvantages. Therefore, developing a method that can address some of these shortcomings is necessary. This research aims to analyze the accuracy and feasibility of leaf area measurement methods using object tuntun and digital image processing. The research method used is to compare leaf area measurement techniques using the leaf constant method, leaf area meter, and method of measuring leaf area with the help of digital image processing-based objects tuntun. Data analysis uses R2, RMSE, NRMSE, NSE, and d. The results showed that the leaf area measurement method using digital image processing-based object tuntun assistance is excellent and accurate, and the results have a robust and linear correlation with leaf area measurements using the leaf constant method and leaf area meter. Therefore, the method of measuring leaf area using the help of digital image processing-based objects tuntun is very feasible to be developed and applied to become one of the methods of calculating leaf area that is accurate, fast, and for various leaf sizes and various types of plants.